2017
DOI: 10.1016/j.drugalcdep.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gambling and substance use among recent college students

Abstract: Background While it is well known that substance use and gambling overlap, the degree to which this overlap can be explained by shared risk factors has not been fully explored. This study aimed to identify common and unique risk factors for gambling and substance use among young adults. Methods Young adults (n=1,019) in a longitudinal study since college entry were interviewed annually. Past-year frequency of seven gambling activities was assessed once (Year 5). Structural equation models evaluated suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
(91 reference statements)
2
20
1
Order By: Relevance
“…The findings indicate that nearly one in two underage school students had had at least one alcoholic drink in the previous month, that one in four smoked, nearly 1 in 5 had consumed cannabis in the previous year and 1 in 15 could be defined as an at risk or problem gambler. These prevalence data are consistent with previous research 24. The particular geographical distribution of the ORs for the prevalence of different health-risk behaviours in Italy was also in line with official records 25 26…”
Section: Discussionsupporting
confidence: 91%
“…The findings indicate that nearly one in two underage school students had had at least one alcoholic drink in the previous month, that one in four smoked, nearly 1 in 5 had consumed cannabis in the previous year and 1 in 15 could be defined as an at risk or problem gambler. These prevalence data are consistent with previous research 24. The particular geographical distribution of the ORs for the prevalence of different health-risk behaviours in Italy was also in line with official records 25 26…”
Section: Discussionsupporting
confidence: 91%
“…Cross-sectional research is commonly used to identify psychosocial factors of GD, including impulsivity (Caldeira et al, 2017;Hartmann & Blaszczynski, 2018;Yang, Zhong, Wu, Li, & Li, 2016), psychopathy (Onyedire et al, 2019), low self-esteem (Kaare, Mottus, & Konstabel, 2009), emotional distress (King, Abrams, & Wilkinson, 2010;Tang, Chua, & Wu, 2011), neuroticism (Tackett, Rodriguez, Rinker, & Neighbors, 2015), and parental gambling problems (King et al, 2010;Winters, Stinchfield, Botzet, & Anderson, 2002). Bishai (2004) found that emerging adults who have reached the legal age for gambling, including university students, have lower level of time preferences (i.e., a greater preference for present utility over future utility) than their older counterparts, which puts them at higher risk for addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion of shared environmental risk factors is also warranted. Peer delinquency demonstrates associations with both alcohol use and gambling frequency (Barnes et al 1999;Caldeira et al 2017). Socioeconomic status and/or accessibility may also contribute to the environmental risk for alcohol use (Tobler et al 2009) and gambling behaviors (Marshall, 2007).…”
Section: Discussionmentioning
confidence: 99%